2019
DOI: 10.4269/ajtmh.18-0396
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Extended-Spectrum β-Lactamase Enterobacteriaceae Isolated from Egyptian Patients with Community- and Hospital-Acquired Urinary Tract Infection

Abstract: Extended-spectrum β-lactamases (ESβLs) pose a serious problem in the treatment of urinary tract infections (UTIs). The ESβL-producing organism is an expanding global health problem. Therefore, screening for ESβL, detection of their drug-resistance pattern, and molecular characterization should be a continuous process. The present study was performed to determine the antibiotic resistance profile and the genetic characterization of ESβL isolates from hospital-and community-acquired UTIs. Two hundred fifty Enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
(47 reference statements)
1
7
2
Order By: Relevance
“…1 a, Supplementary Figure S 3 ), which is in line with other studies [ 39 , 54 – 56 ]. In contrast, our prevalence rate was higher than that reported in earlier Egyptian studies, namely, 17% by [ 57 ] and 38.8% by [ 58 ]. Therefore, an increase in the ESBL production rate has emerged over time in Egypt due to the uncontrolled use of antimicrobials, mostly third-generation cephalosporins, as routine therapy against UTIs [ 59 , 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…1 a, Supplementary Figure S 3 ), which is in line with other studies [ 39 , 54 – 56 ]. In contrast, our prevalence rate was higher than that reported in earlier Egyptian studies, namely, 17% by [ 57 ] and 38.8% by [ 58 ]. Therefore, an increase in the ESBL production rate has emerged over time in Egypt due to the uncontrolled use of antimicrobials, mostly third-generation cephalosporins, as routine therapy against UTIs [ 59 , 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This high frequency is comparable to a recent data reported by Hassuna et al, 2020 in our region, where 57.9% of E. coli isolated from community-acquired UTIs were ESBL producers [ 30 ]. On the other hand, our prevalence of ESBL-producing isolates is quite higher than that reported in several previous Egyptian studies; 17% by Fam et al, 2011 [ 28 ] and 38.8%, by Shash et al, 2019 [ 31 ], suggesting an increasing rate of ESBLs-producing Enterobacteriaceae spread in Egypt, that may be caused by extensive use of 3rd generation cephalosporines as empiric treatment in Egypt. The prevalence of ESBL production varies according to species, geographical areas, variations in infection control programs, different patterns of empiric antibiotic regimens and even over time .…”
Section: Discussioncontrasting
confidence: 71%
“…Global spread of β-lactamases-producing strains gives a great importance to the study of these strains in community and hospitals for reassessment of the existing treatment protocols. In Egypt, multiple studies have investigated the prevalence of ESBLs among Enterobacteriaceae isolated from hospital and community acquired-UTIs [28][29][30] [31], suggesting an increasing rate of ESBLsproducing Enterobacteriaceae spread in Egypt, that may be caused by extensive use of 3rd generation cephalosporines as empiric treatment in Egypt. The prevalence of ESBL production varies according to species, geographical areas, variations in infection control programs, different patterns of empiric antibiotic regimens and even over time.…”
Section: Discussionmentioning
confidence: 99%
“…coli isolates from catheterized patients in the present study are not only characterized by high rates of resistance and biofilm formation but there is also a high rate of expression of bla-CTX-M (100%). This is in agreement with some studies as that of the Egyptian study who detected the bla-CTX-M gene in 98% of isolates 41 . Also, an Indonesian study reported CTX-M-15 gene in more than 89% of isolates 42 .…”
Section: Groupsupporting
confidence: 93%